Analisis Penerapan Metode Pembelajaran Pendidikan Agama Islam di SMP Muhammadiyah 57 Medan - Siregar, Siti Marwiah (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
The purpose of this research is to know the factors considered in selecting the method of learning by Islamic religious education teachers at muhammadiyah first high school, to know the design of the learning method of Islamic education at the muhammadiyah first high school, and to know the reasons teachers using learning methods at the Islamic religious education subjects at the muhammadiyah first high school. The methods used in this research is qualitative ethnographic methods, research is done on the muhammadiyah first high school, which became the source of the data in this study are teachers and students which is a key informant. In the data collection technique using observation, interview and documentation. While the technique to test the validity of the data using triangulation. The results showed that the implementation of the use of the method of teaching at the start of the Select method that will be used yaitunya adapted to the objectives to be achieved and the material to be taught, and teachers ' teaching methods in carrying out prepare learning materials, RPP, Syllabus and other supporting materials, as well as using the method of teaching the teacher easier to teach the subject matter and the students more easily understand the material received.